The Strategy Analysis of Village-Owned Enterprises (BUMDesa) in Business Development Efforts : - - Sugiarti Ramadhan, Tri; Mukhlis , Imam; Noviarakhman Zagladi , Arief (Profesional Muda Cendekia Publishing, 2024)
T Research Aims: The aim of the research is to find out the business competitive strategy in order to maintain business existence in the face of the rise of companies around the Mekar Jaya BUMDesa. Design/methodology/approach: Primary data collection was carried out through in-depth interviews with the information in this study. Secondary data was obtained through literature study, research journals, general description of BUMDesa Mekar Jaya Ngawonggo Village. The research method used is a qualitative descriptive analysis method. The analytical method used is SWOT analysis, IFE matrix, EFE matrix, and SWOT matrix. Research Findings: The results of the IFE and EFE matrices show that the BUMDesa quadrant position is in Quadrant I. This position shows that the profitability is very high BUMDesa has opportunities and strengths to take advantage of existing association opportunities. The recommended strategy is that human resources must be applied even better. Based on the results of this research, the SWOT analysis and the development of strategies implemented can support the welfare of the people of Ngawonggo Village. Theoretical Contribution/Originality: The theoretical contribution of this research lies in its innovative amalgamation of conventional business strategy frameworks with a tailored analytical model designed to capture the intricate dynamics of Village-Owned Enterprises (BUMDesa).